Adaptation of Technological Methods to Climatic Conditions in Agrotechnologies in South Ural - Gulyanov , Yury; Chibilyov, Alexander; Levykin, Sergey (KnE Life Sciences, 2021)
This study aimed to define an optimal sowing date of winter wheat in the steppe zone of South Ural and West Siberia. The effects of climatic factors were determined by analyzing modern climatic resources and experimentally testing in the conditions of the central zone in Orenburgskaya oblast. Research from the All-Russian ScientificResearch Institute of Hydro-meteorological Information – World Data Center (RSRIHIWDC) served as a source of archival meteorological data for 2009-2019. Experimental data were collected through field work on the south chernozem in the Central zone of Orenburgskaya oblast for 2019-2020. Digital material was processed using statistical analysis. It was confirmed that in the Central zone of Orenburgskaya oblast under modern climatic conditions, the period between 25-30 August is the most acceptable date to sow winter wheat. If sowing occurs at later dates, there is a risk of not obtaining the required amount of effective temperatures, which can result in disunited sparse shoots, bushes that are not fully formed, and low phytometric parameters, and therefore a low realization of climatically secured productivity. These results could be more widely tested in other steppe regions of Ural and West Siberia with a prospect to introduce the results into zonal recommendations for production. Keywords: climatic resources, productivity reserves, winter wheat